Pro-Arrhythmic Effect of Chronic Stress-Associated Humoral Factors in Human Induced Pluripotent Stem Cell-Derived Cardiomyocytes - Shi Su; Jinglei Sun; Suhua Qiu; Wenting Wu; Jiali Zhang; Yi Wang; Chenxia Shi; Yanfang Xu (Biology)
Under chronic stress, the pro-arrhythmic effect and mechanism of circulating humoral factors in human cardiomyocytes remain unknown. In the present study, we observed the effect of serum from chronic-stress mice on the electrical activity of human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs). Male C57/BL6J mice were subjected to 35 days of chronic unpredictable mild stress (CUMS). The serum from CUMS mice induced arrhythmia-like events (cell arrhythmias) in hiPSC-CMs in a time- and concentration-dependent manner. Patch clamp recordings in the heterologous expression system demonstrated that the serum derived from CUMS mice exerted an inhibitory effect on the cloned human potassium currents (Ito, IKr, IKs) that mediate action potential repolarization. In addition, serum from CUMS reduced the expression of relevant channel proteins. Moreover, both heat-inactivated serum and deproteinized serum evoked similar severity of cell arrhythmias in hiPSC-CMs as the untreated serum, indicating that circulating substances with small molecules were mainly involved in the occurrence of arrhythmias. Furthermore, metabolomics analysis showed that 90 small-molecule metabolites increased and 390 decreased in CUMS serum. We concluded that circulating humoral substances under chronic stress conditions have direct arrhythmogenic effects by inducing ion channel dysfunction in myocardial cells.